Values in heritage management : emerging approaches and research directions - Values in heritage management (2017 : Getty Conservation Institute); Avrami, Erica C.; Getty Conservation Institute (Los Angeles : The Getty Conservation Institute, 2019)
"This scholarly edited volume examines recent approaches to values-based heritage management and suggests avenues for further research"--Provided by publisher.
Foreword / Jeanne Marie Teutonico -- Background -- Introduction / Erica Avrami, Susan Macdonald, Randall Mason, and David Myers -- Mapping the Issue of Values / Erica Avrami and Randall Mason -- Perspectives from the Field -- Spatializing Values in Heritage Conservation: The Potential of Cultural Mapping / Erica Avrami -- Heritage Work: Understanding the Values, Applying the Values / Kristal Buckley -- The Shift toward Values in UK Heritage Practice / Kate Clark -- Understanding Values of Cultural Heritage within the Framework of Social Identity Conflicts / Karina V. Korostelina -- The Contemporary Values behind Chinese Heritage / Kuanghan Li -- Values-Based Management and the Burra Charter: 1979, 1999, 2013 / Richard Mackay -- Is Conservation of Cultural Heritage Halal? Perspectives on Heritage Values Rooted in Arabic-Islamic Traditions / Hossam Mahdy -- Changing Concepts and Values in Natural Heritage Conservation: A View through IUCN and UNESCO Policies / Josep-Maria Mallarach and Bas Verschuuren -- Valuing Traumatic Heritage Places as Archives and Agents / Randall Mason -- Values and Relationships between Tangible and Intangible Dimensions of Heritage Places / Ayesha Pamela Rogers -- The Paradox of Valuing the Invaluable: Managing Cultural Values in Heritage Places / Tara Sharma -- Heritage Economics: Coming to Terms with Value and Valuation / David Throsby -- From the Inside Looking Out: Indigenous Perspectives on Heritage Values / Joe Watkins -- Appendix: Conclusions and Recommendations of the Symposium Participants -- Further Readings in Heritage Values.
Includes bibliographical references (pages 226-238).
Keywords: Historic preservation; Cultural property -- Protection